2017
DOI: 10.20959/wjpr20178-7853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antiepileptic Activity of Methanolic Extract of Opuntia Ficus Indica Flower in Mice

Abstract: Opuntia ficus indica flowers (L) commonly known as cactus pear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It also offered up to 62.5% protection against seizure at 200 mg/kg which was significant (p < 0.05) as compared to diazepam [ 159 ] 16 Nicotiana tabacum Ar AQ & HME PTZ Random breed albino male mice (18–24 g) 100 Both extracts decreased the onset and severity of seizures (but it is statistically insignificant as compared to the negative control group). Both extracts decreased the mortality of PTZ-treated mice [ 160 ] 17 Olea europaea PTZ Mice weighing (25–30 g) 20 The active constituent of Olea europaea leaf, oleuropein (20 mg/kg), caused a significant increase in seizure latency and a significant decrease in the whole body seizure [ 161 ] 18 Opuntia ficus-indica Fl HME PTZ, MES & STR Swiss albino mice (20–25 g) 250 & 500 Protect the mice against PTZ, MES, and STR-induced seizures [ 135 ] 19 Pentas schimperiana RB HME PTZ & MES Swiss albino mice (20–30 g) 100–400 The BU and ME fractions significantly inhibited the PTZ and MES-induced seizure at 400 mg/kg [ 162 ] 20 Pterolobium stellatum L AQ & HME PTZ & MES Swiss albino mice (25–32 g) 100–400 The HME extract exhibited a dose-dependent increase on the latency onset of seizure against PTZ. In addition, both HME and AQ fractions demonstrat...…”
Section: Pharmacological Evidence Of Reported Medicinal Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also offered up to 62.5% protection against seizure at 200 mg/kg which was significant (p < 0.05) as compared to diazepam [ 159 ] 16 Nicotiana tabacum Ar AQ & HME PTZ Random breed albino male mice (18–24 g) 100 Both extracts decreased the onset and severity of seizures (but it is statistically insignificant as compared to the negative control group). Both extracts decreased the mortality of PTZ-treated mice [ 160 ] 17 Olea europaea PTZ Mice weighing (25–30 g) 20 The active constituent of Olea europaea leaf, oleuropein (20 mg/kg), caused a significant increase in seizure latency and a significant decrease in the whole body seizure [ 161 ] 18 Opuntia ficus-indica Fl HME PTZ, MES & STR Swiss albino mice (20–25 g) 250 & 500 Protect the mice against PTZ, MES, and STR-induced seizures [ 135 ] 19 Pentas schimperiana RB HME PTZ & MES Swiss albino mice (20–30 g) 100–400 The BU and ME fractions significantly inhibited the PTZ and MES-induced seizure at 400 mg/kg [ 162 ] 20 Pterolobium stellatum L AQ & HME PTZ & MES Swiss albino mice (25–32 g) 100–400 The HME extract exhibited a dose-dependent increase on the latency onset of seizure against PTZ. In addition, both HME and AQ fractions demonstrat...…”
Section: Pharmacological Evidence Of Reported Medicinal Plantsmentioning
confidence: 99%
“…Overall, the result suggested that Croton macrostachyus may have a promising effect in secondary GTCS and primary generalized seizures in humans. Opuntia ficus-indica commonly known as cactus pear is used in the treatment of epilepsy in Ethiopia and India [ 135 ]. The in vivo anticonvulsant activity of the flower ME extract was assessed using Swiss Albino mice.…”
Section: Pharmacological Evidence Of Reported Medicinal Plantsmentioning
confidence: 99%